2010
DOI: 10.1007/s13105-010-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of SND1 protein to low density lipid droplets in liver steatosis

Abstract: Although the human homologue of SND p102, p100 coactivator, was initially described as a nuclear protein, the p100 coactivator protein family members have non-nuclear localization in mammalian cells with active lipid handling, storage, and secretion. However, their role in lipid homeostasis remains unresolved. Here, we investigate the distribution of the rat homologue SND p102 (also called SND1) and its association with newly formed lipid droplets in the liver parenchyma and cultured hepatocytes. Sucrose gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…This multifunctional regulator of gene expression has a broad expression profile [41], is enriched in secretory cells [27] and acts as transcriptional co-activator [42], in RNA editing [43], in the generation of RISC [28] and is linked to apoptosis [44]. SND1 is generally regarded as a nuclear and/or cytoplasmic protein and in line with a number of reports, [26,45,46] we observed only extranuclear expression in b-cells. The defined architecture of SND1 provides distinct binding sites and functions [47].…”
Section: Discussionsupporting
confidence: 88%
“…This multifunctional regulator of gene expression has a broad expression profile [41], is enriched in secretory cells [27] and acts as transcriptional co-activator [42], in RNA editing [43], in the generation of RISC [28] and is linked to apoptosis [44]. SND1 is generally regarded as a nuclear and/or cytoplasmic protein and in line with a number of reports, [26,45,46] we observed only extranuclear expression in b-cells. The defined architecture of SND1 provides distinct binding sites and functions [47].…”
Section: Discussionsupporting
confidence: 88%
“…Palacios et al (25) first reported that overexpression of Snd p102, a rat homolog of p100 coactivator, promotes the secretion of lipoprotein phospholipids in primary hepatocytes. They further demonstrated that Snd p102 was present in newly formed lipid droplets in the liver parenchyma and cultured hepatocytes (26). In the current study, the livers of HFD-Tg mice displayed lower TG accumulation (steatosis) in vivo.…”
Section: Discussionsupporting
confidence: 68%
“…Owing to a high protein-protein binding affinity coexisting with enzymatic activity, Tudor-SN can exert its biochemical function by acting as a scaffolding molecule for large multiprotein complexes, as a nuclease, or both (22). In terms of the function of Tudor-SN in lipid metabolism, it has been found in the cytosolic lipid droplets of lactating mammary glands of cows and mice (24) and acts as a factor to promote lipoprotein phospholipid localization in lipid droplets in rat hepatocytes (25,26). Furthermore, Tudor-SN has been demonstrated to be a determinant of the downstream effector of TNF-a, which contributes to glycerophospholipid homeostasis in human hepatoma HepG2 cells (27).…”
mentioning
confidence: 99%
“…SND1 interacts with a lipoprotein part of the fatty acid synthase (FASN) complex to form LDs. Under steatogenic conditions, SND1 is targeted from cell compartments like the ER and golgi complex to low density LDs to facilitate their assembly [55] .…”
Section: Role Of Snd1 In Lipid Metabolismmentioning
confidence: 99%